COMPARISON OF MILK YIELD, FAT, AND PROTEIN CONTENT OF IMPORTED FRIESIAN HOLSTEIN COWS AT BATURRADEN, BANYUMAS, INDONESIA - Dian Kurniawati; Teguh Rafian; Kusuma Adhianto (Universitas Muhammadiyah Malang, 2026)
This study aimed to evaluate the effects of the origin of imported Friesian Holstein cows (New Zealand and Australia) on milk yield, milk fat percentage, and milk protein percentage. The study was conducted at the Breeding Center for Superior Livestock and Forage Crops (BPTU-HPT) Baturraden, Banyumas, Indonesia. A total of 100 Friesian Holstein cows were used, consisting of 19 cows imported from New Zealand and 81 cows imported from Australia. Secondary data on milk yield, milk fat percentage, and milk protein percentage were obtained from farm records. Milk yield was standardized to a 305 day mature equivalent (ME) basis. Data were analyzed using an independent samples t-test. The results showed that the origin of imported Friesian Holstein cows significantly affected (P<0.05) milk yield, milk fat percentage, and milk protein percentage. Friesian Holstein cows imported from New Zealand produced 4,450 L ± 1,746 L of milk, with milk fat and protein percentages of 3.90%± 0.59% and 2.94% ± 0.06%, respectively. In contrast, cows imported from Australia produced 5,583 L ± 1,775 L of milk, with milk fat and protein percentages of 4.70% ± 0.72% and 3.23±0.40%, respectively. The overall averages for milk yield, milk fat percentage, and milk protein percentage were 5,016 L± 1,760 L, 4.30%±0.65%, and 3.08%±0.23%, respectively. In conclusion, Friesian Holstein cows imported from Australia exhibited greater milk yield and higher milk fat and protein percentages than those imported from New Zealand under the management conditions of BPTU-HPT Baturraden, Banyumas.